2012
DOI: 10.2298/hel1257087s
|View full text |Cite
|
Sign up to set email alerts
|

Race composition and distribution of broomrape (Orobanche cumana Wallr.) in Bulgaria during 2007-2011

Abstract: In order to determine the race composition and distribution of broomrape in Bulgaria during the period 2007 -2011, samples (seeds) of the parasite were collected in 116 different locations from the main sunflower production regions. The collected seeds were used to infect differential sets of genotypes by a standard methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Therefore it becomes evident that the virulence of the new populations of the Guadalquivir Valley area is different to races G populations from Eastern Europe. We are accordingly naming the new populations as a local race G of the Guadalquivir Valley (G GV ) to differentiate its level of virulence from the currently predominant race F GV and from races G described for other areas such as Turkey (Kaya et al, 2004), Bulgaria (Shindrova and Penchev, 2012), Romania (Pacureanu-Joita et al, 2009), Russia (Antonova et al, 2013), China (Shi et al, 2015), Greece, and Ukraine (present study). This study also concluded that the inbred line P-96 is not valid as differential line between races F GV and G GV , as it is resistant to both groups of populations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it becomes evident that the virulence of the new populations of the Guadalquivir Valley area is different to races G populations from Eastern Europe. We are accordingly naming the new populations as a local race G of the Guadalquivir Valley (G GV ) to differentiate its level of virulence from the currently predominant race F GV and from races G described for other areas such as Turkey (Kaya et al, 2004), Bulgaria (Shindrova and Penchev, 2012), Romania (Pacureanu-Joita et al, 2009), Russia (Antonova et al, 2013), China (Shi et al, 2015), Greece, and Ukraine (present study). This study also concluded that the inbred line P-96 is not valid as differential line between races F GV and G GV , as it is resistant to both groups of populations.…”
Section: Discussionmentioning
confidence: 99%
“…Sunflower populations that were resistant to race F broomrape were also found in 2002 [20]. However, new broomrape populations, named races G and H [21][22][23], that overcome race F resistance sunflower genes are currently present in Eastern countries such as Turkey, Romania, Bulgaria, and Russia [19]. The speed with which these races of parasitic plants overcame the sunflower resistance is a result of the existence of a single mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, all of them were named as race F though the relationship between the different F races has not been studied. Nowadays, populations overcoming resistance sources to race F, named as races G and H, have been identified in most of these countries (Kaya et al, 2009; Pacureanu-Joita et al, 2009; Shindrova and Penchev, 2012; Antonova et al, 2013; Martín-Sanz et al, 2016). As mentioned for race F, no comparative studies have been conducted between races G and H reported in different countries.…”
Section: Introductionmentioning
confidence: 99%